PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PENDEKATAN KONSTRUKTIVISME PADA MATERI SISTEM PENCERNAAN MAKANAN DAN BAHAN KIMIA DALAM KEHIDUPAN KELAS VIII SMP - Auliya, Annisa; ', Yustina; Ahmad, Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract Has conducted research and development of student worksheets (LKPD) based constructivism approach on the contens for digestive system and chemicals in life ofÂ IPA class VIII junior high school. There are five LKPD based constructivist approach developed. This research was conducted at the Laboratory PMIPA of Biology Department of the University of Riau and SMPN 1 Pekanbaru until Desember 2016. This type of research is the development with ADDIEâ€™s model of integration to the stage of development. Instruments of data collection in this study is the assessment sheet/validation LKPD and student questionnaire responses. After LKPD developed, validated by 4 validator and then do the first test at 22 student in the 5th semester of biology education FKIP UR, and thesecond test at 20 students of Class VIII at SMPN 1 Pekanbaru. The result shoowed the average score feasibility aspects of the content of 5 LKPD developed is 3.42 very valid category, the mean score of the designing aspect is 3.32 category of very valid, and the mean score is 3.33 pedagogic aspect is very valid category. The mean overall score of the fifth LKPD is 3.35 very valid category. The results of the questionnaire responses in the firsttest showed a mean score of 91 with very good categories and the results of questionnaires in the secondtest showed a mean score of 91 with very good category. The results of the analysis of the answers of students in LKPD 1 and 4 showed the average value of both 3.27 good categories and 3.35 good categories. It can be concluded that LKPD Based constructivist approach on the contens for digestive system and chemicals in life ofÂ IPA class VIII junior high school as well as fit for use in science teaching in schools could provide insight and knowledge.